The potential of agro based nanomaterials for nanofilters to capture suspended titanium nanoparticles in the air - Shamsul Harumain, Zakuan Azizi; Zahaba, Maryam; Danial, Wan Hazman (National Institute of Occupational Safety and Health (NIOSH), 2021)
Nanomaterials have a wide range of new technologies and industrial use and have created many new products and employment opportunities. However, they can also pose unknown risks and specific uncertainties in occupational safety and health issues. The latest and most worrying issue involves the increasing production and nanoparticles, particularly titanium dioxide (TiO2). Therefore, a rigorous study should be carried out to obtain more intensive information to develop a new technique for personal exposure monitoring. The commercially available nanoparticle respiratory deposition (NRD) sampler usually occupied with nylon filter contains TiO2 background material and is rather expensive. As an alternative, agro based nanofilters were developed from nanomaterials synthesized from rice husks, namely, nanosilica and nanozeolite embedded on/in a polyvinylidene fluoride (PVDF) membrane. As a comparison, graphene was also used to produce nanofilters due to its outstanding performance in chemical absorption. Analysis using Field Emission Scanning Electron Microscope (FESEM) showed a formation of cracks on both nanofilters when embedded with 1% w/v of either nanosilica and nanozeolite compared to 0.1 and 0.5 % w/v. Agglomerate of nanosilica particles with the size between 20 – 40 nm and nanozeolite with the size between 18 – 30 nm were identified on the developed nanofilter. Energy Dispersive X-ray (EDX) confirmed the presence of functional groups such as silica, oxide, sodium, alumina, and carbon on the developed nanofilters, further confirming the deposition of the nanomaterials on the PVDF membrane. Further investigation on the ability to capture titanium nanoparticles using 0.1 % w/v nanofilters from both materials showed that all filters tested could capture titanium nanoparticles with nanozeolite filters showing the highest accumulation with 9170 mg/m3. These results suggest that agro-based nanomaterials can be used as nanofilters to capture titanium nanoparticles in the air.